2021
DOI: 10.3390/ijerph18105113
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Contributors to Neurodegeneration: An Exploration of the Effects of Alcohol on Clinical Features of Huntington’s Disease Using the Enroll-HD Global Platform

Abstract: Huntington’s disease (HD) is a neurodegenerative dementia with a well recognised genetic cause. Alcohol misuse is a major environmental factor relevant to numerous neurological presentations, including HD. We explored the effects of alcohol intake on clinical features of HD by means of data from the Enroll-HD, which is a global registry study. A retrospective observational study making use of the Enroll-HD periodic dataset up to 2020 (in accordance with the Enroll-HD guidelines, encompassing 16,120 subjects wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Moreover, future studies should include larger samples of individuals with premanifest HD, as neurodegeneration in this population can be influenced by several variables other than sleep, such as medication use and alcohol consumption. 14 Larger sample sizes would also enable moderation analyses on the role of the CAG expansion on associations between NfL and sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, future studies should include larger samples of individuals with premanifest HD, as neurodegeneration in this population can be influenced by several variables other than sleep, such as medication use and alcohol consumption. 14 Larger sample sizes would also enable moderation analyses on the role of the CAG expansion on associations between NfL and sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of substance misuse, self-harm and suicide are higher in the HD population than in the general population and rates of addiction often increase with disease progression. 8 …”
Section: Presentation and Investigation Of Hdmentioning
confidence: 99%
“…Despite considerable research into disease‐modifying drugs, only environmental factors have been shown to impact disease progression. 6 , 7 , 8 Moreover, disease trajectories differ between individuals with similar genotypic profiles and age at onset, 9 , 10 suggesting an influence of sociodemographic factors, 11 , 12 , 13 , 14 , 15 health behaviors, 11 , 16 , 17 , 18 , 19 or health history 11 , 20 , 21 , 22 on which intervention might have a positive impact. Identifying modifiable factors on which to act as early as possible is important to ensure the maximum effect of interventions and preserve a good quality of life for as long as possible.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a high educational level is associated with an early diagnosis 12 but also slower disease progression. 13 Health behaviors such as high alcohol consumption, 16 tobacco use, 18 coffee consumption, 23 and low body mass index (BMI) 19 are associated with more rapid disease progression as are musculoskeletal, 24 cardiovascular, 25 , 26 neurological, 27 or psychiatric comorbidities, 20 and a history of depression and anxiety. 21 However, these associations remain unclear, and the evidence contrasted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation